BENIGN PROSTATIC HYPERPLASIA AND PROSTATE CANCER: A COMPREHENSIVE COMPARATIVE REVIEW (International journal of medical sciences, 2026)
Benign Prostatic Hyperplasia (BPH) and Prostate Cancer are highly prevalent prostate disorders in aging men. Although both conditions often present with similar lower urinary tract symptoms, they differ fundamentally in pathophysiology, biological behavior, prognosis, and treatment strategies. This article provides a comprehensive scientific comparison of clinical manifestations, diagnostic methods, and therapeutic approaches for BPH and prostate cancer.